Peran Transparansi Financial Decision dalam Memediasi Pengaruh Financial Attitude terhadap Financial Well-Being (Penerima KIP Kuliah) - Syahrul Nasarudin; Mira Mira; Masrullah Masrullah (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2026)
This study aims to analyze the mediating role of financial decision transparency in the relationship between financial attitude and financial well-being among KIP Kuliah recipients at Universitas Muhammadiyah Makassar. As a government-funded educational assistance program, KIP requires responsible financial management to enhance students’ financial well-being. However, positive financial attitudes do not automatically lead to financial well-being without transparent financial decision-making practices. This study employs a quantitative approach using Partial Least Squares-Structural Equation Modeling (PLS-SEM). Primary data were collected through questionnaires distributed to KIP recipients. The analysis included validity, reliability, and hypothesis testing using bootstrapping techniques. The results indicate that financial attitude has a significant positive effect on financial decision transparency. Financial decision transparency also has a significant positive effect on financial well-being. Furthermore, financial decision transparency partially mediates the relationship between financial attitude and financial well-being. These findings suggest that students’ financial well-being improves when positive financial attitudes are translated into transparent and accountable financial decisions.